VIKOR multi-criteria decision making with AHP reliable weighting for article acceptance recommendation - Aji Prasetya Wibawa; Juwita Annisa Fauzi; Seno Isbiyantoro; Rahmat Irsyada; Dhaniyar Dhaniyar; Leonel Hernandez (Universitas Ahmad Dahlan, 2019)
DSS is built to support the solution recommendation of a problem. AHP and VIKOR are examples of DSS method. Due to VIKOR’s subjective weighting, this study combines the AHP and VIKOR approach to create a better and more reliable decision support system. The DSS is used to recommend article acceptance using five criteria: originality, quality, clarity, significance, and relevance. The results showed that AHP-VIKOR outperforms the performance of VIKOR. AHP weighting reliably replaces the subjective VIKOR’s initial weighting. The AHP-VIKOR result is more accurate and steadier than VIKOR. Thus, AHP-VIKOR can be presented as a proposed approach for creating a recommendation of scientific article acceptance.